2018
DOI: 10.5194/angeo-36-1161-2018
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the NeQuick model performance under different geomagnetic conditions over South Africa during the ascending phase of the solar cycle (2009–2012)

Abstract: Abstract. In order to provide a scientific base to the NeQuick characterisation under disturbed conditions, the comparison of its performance for quiet and storm days is investigated in the southern mid-latitude. This investigation was realised using the two versions of the NeQuick model which were adapted to local and storm-specific response by using the critical frequency of the F2 layer (foF2) and the propagation factor (M(3000)F2) derived from three South African ionosonde measurements, Hermanus (34.40∘ S,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Twinomugish et al ( 2017) also reported a similar result over the east African equatorial region. Ahoua et al (2018) also concluded that the NeQuick model has comparable reliability in quiet and disturbed days; somewhat, its accuracy is affected by solar activity (better in moderate than in high solar activity). During the storm's main phase, an interplanetary electric field penetrates the ionospheric area for several hours, loading interplanetary particles into the ionosphere (Kumar and Singh, 2010).…”
Section: Disturb Day Variationmentioning
confidence: 93%
See 1 more Smart Citation
“…Twinomugish et al ( 2017) also reported a similar result over the east African equatorial region. Ahoua et al (2018) also concluded that the NeQuick model has comparable reliability in quiet and disturbed days; somewhat, its accuracy is affected by solar activity (better in moderate than in high solar activity). During the storm's main phase, an interplanetary electric field penetrates the ionospheric area for several hours, loading interplanetary particles into the ionosphere (Kumar and Singh, 2010).…”
Section: Disturb Day Variationmentioning
confidence: 93%
“…Researchers (Ezquer et al, 2018;Okoh et al, 2018;Teriku, 2020) conducted a comparison of different ionospheric TEC models (IRI, IRI-plas, and NeQ-2) using GNSS measurements and concluded that NeQ-2 performs better than other models regardless of time or location. Ahoua et al (2018) compared observed 4 TEC derived from a nearby GNSS dual-frequency receiver to the NeQ-2 model performance for quiet and storm days over south Africa during the ascending phase of the solar cycle (2009)(2010)(2011). Yu et al (2012) evaluated the monthly average of the NeQ-2 model over China during the quietest period and discovered that the NeQ-2 predicts GPS TEC accurately (except for few cases).…”
Section: Introductionmentioning
confidence: 99%
“…'49' refers to the SNR and *78 is the checksum data and always begin with *. Since the sentence contained four satellites propagation data, thus, the numbers will be repeated continuously for the other satellite in view [8], [11].…”
Section: Table 1 -1-band Frequencies Range Unitsmentioning
confidence: 99%
“…This shows that the geomagnetic storm observed during 7 April 2000 was driven by a Corona Mass Ejection (CME). Geomagmetic storms have great influence on the earth's ionosphere and it usually leads to changes in ionospheric density structure (Ahoua et al, 2015). The sharp and rapid changes in Total Electron Content (TEC) are very important conditions for eruptions of ionospheric plasma density irregularities which invariably causes scintillations in radio waves (Akala et al, 2013).…”
mentioning
confidence: 99%